Sawdust as an ameliorant to decontaminate Arsenic in potato soils - Md. Hossain; Tuhin Roy; Maruf Mostofa (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Bangladesh is an agriculture-based country, where about 3 million ha is covered by groundwater sources for irrigation, but a significant portion of irrigation water is Arsenic contaminated. To produce Potato under Arsenic contaminated soil, an experiment was conducted to find out the effect of sawdust as an adsorbent to decontaminate Arsenic toxicity in soil. Method The research was conducted in pot experiment. It consisted of two factors. Factor A: Arsenic levels (4) viz., As0: control (0 mg/kgsoil), As1: 25 mg/kg soil, As2: 50 mg/kg soil, and As3: 75 mg/kg soil. Factor B: Sawdust levels (4) viz., S0: control (0 g/kg soil), S1: 10 g/kg soil, S2: 50 g/kg soil, and S3: 100 g/kg soil. Results Arsenic content in Potato tuber peel and flesh gradually increased with the increase of Arsenic levels. As3 was found for the highest accumulation of Arsenic in tuber peel (3.867 mg/kgfresh weight) and flesh (0.6236 mg/kgfresh weight). Arsenic content in both peel and flesh of Potato tuber decreased with increasing sawdust levels. The soil treated with S3 reduced 86.41% and 51.44% Arsenic accumulation from tuber peel and flesh, respectively, compared to control (S0). Potato produced from the treatment As1S1 accumulated a lower amount of Arsenic (0.15 mg/kgfresh weight) in Potato flesh compared to those of other treatments. Conclusion Therefore, Potato growers can produce Potato in 25 mg/kg Arsenic contaminated soil treated with 10 g sawdust/kg soil, which contains a minimum than the critical level of Arsenic for human consumption.